Looking for evidence that place of residence influenced visitor attitudes to feeding wild dolphins - Jessica Patroni; Alicia Day; Diane Lee; Jennifer Kim Lian Chan; David Kerr; David Newsome; Greg D Simpson (ResearchGate, 2018)
Purpose – To ascertain if place attachment or experiential norms influence visitor attitudes to the feeding of wild dolphins. Design/Methodology/Approach – A cross section of beach based visitors at a popular Australian marine tourism destination were opportunistically sampled using pen and paper questionnaires. Findings – Visitors expressed strong support for the strictly controlled minimalist reward feeding that accompanies beach based wild dolphin interactions at the Bunbury Dolphin Discovery Centre and visitors believe there are tourism benefits to be gained from the regulated feeding of wild dolphins. Results also suggest that neither place attachment nor experiential norms influence visitor attitudes to feeding of the Koombana Bay dolphin population. Originality of the research – This location specific, snapshot, case study suggests that contrary to published theory, place attachment and experiential norms do not influence tourist attitudes to wildlife feeding, especially for charismatic iconic wildlife such as dolphins. The full text of this open access article can be accessed at http://hrcak.srce.hr/192160